2016
DOI: 10.1177/000313481608200730
|View full text |Cite
|
Sign up to set email alerts
|

Vital Signs Strongly Predict Massive Transfusion Need in Geriatric Trauma Patients

Abstract: Early recognition of massive transfusion (MT) requirement in geriatric trauma patients presents a challenge, as older patients present with vital signs outside of traditional thresholds for hypotension and tachycardia. Although many systems exist to predict MT need in trauma patients, none have specifically evaluated the geriatric population. We sought to evaluate the predictive value of presenting vital signs in geriatric trauma patients for prediction of MT. We retrospectively reviewed geriatric trauma patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Isolated vital signs, such as HR or SBP, are unreliable in the assessment of hypovolemic shock. HR alone does not predict the need for MT [11,22]. In contrast, SI has been shown to better risk-stratify patients for critical bleeding, increased transfusion requirements and early mortality [11,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolated vital signs, such as HR or SBP, are unreliable in the assessment of hypovolemic shock. HR alone does not predict the need for MT [11,22]. In contrast, SI has been shown to better risk-stratify patients for critical bleeding, increased transfusion requirements and early mortality [11,23].…”
Section: Discussionmentioning
confidence: 99%
“…Bruijns et al reported that the use of the difference between ED and prehospital SBP, respiratory rate, and SI is good predictor of 48-hours mortality in trauma and may supplement decisions on trauma treatment [24]. Fligor et al reported that MT in geriatric trauma patients can be reliably and simply predicted by the arrival vital signs of SBP, pulse pressure, diastolic blood pressure, and SI [22]. The majority of studies have assessed predictive properties of the SI for patients to require at least 10 units PRBC in the rst 24 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated vital signs, such as HR or SBP, are unreliable in the assessment of hypovolemic shock. HR alone does not predict the need for MT [11,22]. In contrast, SI has been shown to better riskstratify patients for critical bleeding, increased transfusion requirements and early mortality [11,23].…”
Section: Discussionmentioning
confidence: 99%
“…Bruijns et al reported that the difference between ED and prehospital SBP, respiratory rate, and SI are good predictor of 48-hours mortality in trauma and may supplement decisions on trauma treatment [24]. Fligor et al reported that MT in geriatric trauma patients can be reliably and simply predicted by the arrival vital signs of SBP, pulse pressure, diastolic blood pressure, and SI [22]. Most studies have assessed predictive properties of SI for requiring at least 10 units of PRBC in the rst 24 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Vital signs alone have proven insufficient in reliably predicting need for MT [2, 3]. The shock index (SI), the ratio of heart rate (HR)/ systolic blood pressure (SBP), has been considered as a marker for significant injury in trauma patients with hypovolemic shock [4], requirement for transfusion [5], and need for MT [3, 6, 7]. The dynamic change in the ratio of HR to SBP reflect the physiological response of an individual to the trauma injury [812].…”
Section: Introductionmentioning
confidence: 99%